2000
DOI: 10.1038/71709
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for spinal muscular atrophy

Abstract: The survival motor neuron gene is present in humans in a telomeric copy, SMN1, and several centromeric copies, SMN2. Homozygous mutation of SMN1 is associated with proximal spinal muscular atrophy (SMA), a severe motor neuron disease characterized by early childhood onset of progressive muscle weakness. To understand the functional role of SMN1 in SMA, we produced mouse lines deficient for mouse Smn and transgenic mouse lines that expressed human SMN2. Smn-/- mice died during the peri-implantation stage. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
613
4
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(635 citation statements)
references
References 26 publications
17
613
4
1
Order By: Relevance
“…It has been reported that edematous swelling of tissue in other body parts (eg, tail) occurs as part of the phenotype, which was interpreted as a result of progressive failure of the muscle pump to transport venous blood proximally. 40 Disturbance of the insulin-like growth factor 1 axis has been proposed as explanation for the dwarf-like phenotype of older animals. 18,58,59 It is possible that the gastrointestinal involvement at least contributes to the diminished growth in SMA animals and impedes effective oral drug treatment in later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that edematous swelling of tissue in other body parts (eg, tail) occurs as part of the phenotype, which was interpreted as a result of progressive failure of the muscle pump to transport venous blood proximally. 40 Disturbance of the insulin-like growth factor 1 axis has been proposed as explanation for the dwarf-like phenotype of older animals. 18,58,59 It is possible that the gastrointestinal involvement at least contributes to the diminished growth in SMA animals and impedes effective oral drug treatment in later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…SMA mice are described in detail and were bred as previously reported with 50% of the offspring being SMA mice (Smn À/ À ;SMN2 tg/0 ) and 50% control carriers (Smn À/ þ ;SMN2 tg/0 ). 30 Mice carrying homozygously the SMN2 transgene on exon 7 disrupted murine Smn background (Smn À/ À ; SMN2 tg/tg ) 40 fail to develop any motor SMA phenotype, are fertile and live for 41 year, but develop a short and thickened necrotic tail and necrotic ears. Mice heterozygous for the SMN2 transgene on exon 7 disrupted murine Smn background (Smn À/ À ;SMN2 tg/0 ) developed a severe SMA phenotype with a mean age of survival of B10 days.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…Mice with eight copies of human SMN2 are phenotypically normal. [10][11][12][13] The promoters, introns, and flanking regions for SMN1 and SMN2 have been completely sequenced and are almost identical. Transcription assays comparing the SMN promoters implied that the two are transcriptionally equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…Mice have the SMN1 gene but not SMN2, and Smn -/-mouse embryos die during implantation in utero. However, if the human SMN2 gene is placed into the Smn -/-mouse genetic background, the mice survive and exhibit an SMA-like phenotype, with changes in the spinal cord and muscle weakness 3 . The NAIP gene is located next to SMN1 and is often deleted along with SMN1 in SMA patients.…”
mentioning
confidence: 99%